Impedance Spectroscopy Advanced Applications: Battery Research, Bioimpedance, System Design - Kanoun, Olfa (De Gruyter, 2019)
This book covers new advances in the field of impedance spectroscopy including fundamentals, methods and applications. It releases selected extended and peer reviewed scientific contributions from the International Workshop on Impedance Spectroscopy (IWIS 2017) focussing on detailed information about recent scientific research results in electrochemistry and battery research, bioimpedance measurement, sensors, system design, signal processing.